Sin remedio; P.N.; DDF; Cartesiana; Becqueriana; Mil gracias; Calderoniana; Lo dijo Monsi; Monterroseana; Insectario; El día - Huerta, Efraín (Cuadernos Fronterizos, 2018)
Selección de poemas de Efraín Huerta.